Penguatan IRT Ayam Potong Melalui Peningkatan Kualitas Produk dan Pengelolaan Usaha - Mahendra, Tubagus; Novia Ari Sandra; I Komang Dharmendra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This community service program aims to empower household-scale chicken meat vendors by improving product quality and business management. The partner is a housewife who runs a small-scale chicken meat business without refrigeration tools or financial management knowledge. The methods employed were training, mentoring, and the provision of basic equipment adapted to the partner's needs. The partner was also facilitated with a bookkeeping/financial recording application using Microsoft Excel, as requested. Additionally, recommendations were given to separate personal and business expenses so that business development could be measured more accurately. The partner received guidance on how to maintain the quality of the chicken and increase product appeal to customers by processing quality products.Furthermore, supporting equipment such as a simple refrigeration unit was provided to help extend the freshness of the products. According to the partner, after using the freezer for storing the chicken, there were no more incidents of spoiled meat being sold, which previously occurred. As a result, the quality of the chicken products remained 100 percent preserved at the time of sale.